Transferability of principles of evidence based medicine to improve educational quality: systematic review and case study of an online course in primary health care. Issue 7381 (18th January 2003) - Greenhalgh, Trisha; Toon, Peter; Russell, Jill; Wong, Geoff; Plumb, Liz; Macfarlane, Fraser
Abstract : The success of evidence based medicine has led to pressure to make medical education more evidence based. Greenhalgh and colleagues tested the transferability of these principles when developing a postgraduate course